KORELASI KEPEMIMPINAN TRANSFORMASIONAL DENGAN MUTU PENDIDIKAN SEKOLAH MENENGAH ATAS DI KOTA CILEGON - Maullidina, Kiki; Suherman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT "This study aims to analyze the relationship between transformational leadership of school principals and the quality of education in senior high schools (SMA) in Cilegon City. The research employs a quantitative approach using Pearson correlation analysis. Data were collected through closed questionnaires and document studies, involving 50 teachers as respondents selected through a total sampling technique. The independent variable in this study is transformational leadership, while the dependent variable is the quality of education. The results indicate that the data is normally distributed, the relationship between the independent and dependent variables is linear, and the data variance is homogeneous. Pearson correlation analysis yielded an rrr value of 0.571 with a significance level of 0.000 (<0.05), indicating a moderate positive correlation between transformational leadership and the quality of education. These findings affirm that transformational leadership by school principals significantly contributes to improving education quality. The conclusion of this study emphasizes the importance of strengthening transformational leadership as part of the strategy to enhance the quality of education in senior high schools in Cilegon City. The findings are expected to serve as a foundation for developing more effective leadership programs to comprehensively improve educational outcomes.